Comparative Efficiency of Different Weed Management Practices on Economics as well as Nutrient Uptake in Maize - Kantwa, Suman; Jadon, C. K.; Ram, Baldev; Kantwa, S. R.; Tetarwal, J. P.; Kantwa, S. L.; Yadav, L. R.; Yadav, R. K. (International Journal of Economic Plants, 2023)
A field experiment was conducted at Research Farm of Agricultural Research Station, Ummedganj, Kota (Agriculture University, Kota), Rajasthan, India during kharif 2019 to find out the most effective herbicide combination for limiting the menace of weeds in maize. Results showed that application of herbicides observed highest net returns, B: C ratio and nutrient uptake. Among herbicides, atrazine 500 g a.i. ha-1 (PE) fbtopramezone 25.2 g a.i.ha-1 at 20-25 DAS fetched significantly highest net returns of `54984 ha-1 being at par with atrazine 500 g a.i. ha-1 (PE) fbtembotrione 120.75 g a.i. ha-1 at 20-25 DAS (`52500 ha-1), over rest of the treatments under investigation. Furthermore, maximum and significantly higher Benefit: cost ratio was obtained in treatment receiving atrazine 500 g a.i. ha-1 (PE) fbtopramezone 25.2 g a.i. ha-1 at 20-25 DAS (3.42).A weedy crop resulted least nutrient uptake than weed free crop.The highest nutrient uptake (kg ha-1) was recorded under treatment receiving two hand weeding at 20 and 40 DAS followed by atrazine 500 g a.i. ha-1 (PE) fbtopramezone 25.2 g a.i. ha-1 at 20-25 DAS. Treatment two hand weeding at 20 & 40 DAS being at par with atrazine 500 g a.i. ha-1 (PE) + hand weeding at 30 DAS with in situ mulching with weeds, atrazine 500 g a.i. ha-1 (PE) fbtembotrione 120.75 g a.i. ha-1 at 20-25 DAS, and atrazine 500 g a.i. ha-1 (PE) fbtopramezone 25.2 g a.i. ha-1 at 20-25 DAS recorded significantly highest nutrient uptake in grain, stover and total over rest of the treatments under investigation. Minimum nitrogen uptake was obtained under treatment weedy check.Thus, pre-emergence application of atrazine 500 g a.i. ha-1 (PE) followed by topramezone 25.2 g a.i. ha-1 at 20-25 DAS is recommended for highest net returns and nutrient uptake of maize.